Synthesis‐Controlled Polymorphism and Optical Properties of Phyllosilicate‐Analogous Borosulfates M[B2(SO4)4] (M=Mg, Co). Issue 64 (7th October 2020) - Netzsch, Philip; Pielnhofer, Florian; Glaum, Robert; Höppe, Henning A.
Abstract: Increased synthetic control in borosulfate chemistry leads to the access of various new compounds. Herein, the polymorphism of phyllosilicate‐analogous borosulfates is unraveled by adjusting the oleum (65 % SO3 ) content. The new polymorphs β‐Mg[B2 (SO4 )4 ] and α‐Co[B2 (SO4 )4 ] both consist of similar layers of alternating borate and sulfate tetrahedra, but differ in the position of octahedrally coordinated cations. The α‐modification comprises cations between the layers, whereas in the β‐modification cations are embedded within the layers. With this new synthetic approach, phase‐pure compounds of the respective polymorphs α‐Mg[B2 (SO4 )4 ] and β‐Co[B2 (SO4 )4 ] were also achieved. Tanabe–Sugano analysis of the Co 2+ polymorphs reveal weak ligand field splitting and give insights into the coordination behavior of the two‐dimensional borosulfate anions for the first time. DFT calculations confirmed previous in silico experiments and enabled an assignment of the polymorphs by comparing the total electronic energies. The compounds are characterized by single‐crystal XRD, PXRD, FTIR, and UV/Vis/NIR spectroscopy, thermogravimetric analysis (TGA), and density functional theory (DFT) calculations. Abstract : Controlling polymorphism : Sophisticated synthesis strategies enable a targeted access to different polymorphs in M [B2 (SO4 )4 ] ( M =Mg, Co). Both polymorphs comprise phyllosilicate‐analogous topology with corner‐sharing borate and sulfate tetrahedra and differ in the position of the octahedrally coordinated cations. Tanabe–Sugano analysis of the UV/Vis/NIR spectra of α‐ and β‐Co[B2 (SO4 )4 ] revealed a weak ligand field splitting of the borosulfate anion.